Country-specific psychopharmacological risk of reporting suicidality comparing 38 antidepressants and lithium from the FDA Adverse Event Reporting System, 2017–2023 - Eugene, Andy Roger (Frontiers in Psychiatry, 2024)
The United States Food and Drug Administration maintains a black-box warning for antidepressants warning of an increased risk of suicidality in children and young adults that is based on proprietary clinical trial data from study sponsors that was submitted for regulatory approval. This article aims to assess whether the black-box warning for antidepressants is still valid today using recent drug safety data.Methods: Post-marketing adverse drug event data was obtained from the U.S. FDA's Adverse Event Reporting System (FAERS) for years the 2017 through 2023. Logistic regression analysis was conducted using the case versus non-cases methodology and adjusted for gender, age-group, drug role (primary drug, secondary drug, interacting drug, and concomitant drug), initial FDA reporting year, reporter country, and an interaction between drug*agegroup.In the multivariate analysis, compared to fluoxetine and patients aged 25-to 64-year-old, children (adjusted reported odds ratio [aROR] = 7.38, 95% CI, 6.02-9.05) and young-adults (aROR = 3.49, 95% CI, 2.65-4.59) were associated with an increased risk of reporting suicidality, but not for the elderly (aROR = 0.76, 95% CI, 0.53-1.09).Relative to fluoxetine, esketamine had a highest rate of reporting suicidality in children (aROR = 3.20, 95% CI, 2.25-4.54); however, esketamine was associated with a lower risk of reporting suicidality in young adults (aROR = 0.59, 95% CI, 0.41-0.84), and not significant in the elderly (aROR = 0.77, 95% CI, 0.48-1.23). For country-specific findings, relative to the USA, the Slovak Republic, India, and Canada had the lowest risk of reporting suicidality.For the overall study population, desvenlafaxine (aROR = 0.61, 95% CI, 0.46-0.81) and vilazodone (aROR = 0.56, 95% CI, 0.32-0.99) were the only two antidepressants associated with a reduced risk of reporting suicidality.This study shows that with recent antidepressant drug safety data, the U.S. FDA's black-box warning for prescribing antidepressants in children and young adults is valid today in the USA. However, relative to the USA, 15 countries had a significantly lower risk reporting suicidality while 16 countries had a higher risk of reporting suicidality among 38 antidepressants and lithium.